Herding and Contrarian Behavior in Financial Markets - An Internet Experiment - Mathias Drehmann; Jörg Oechssler; Andreas Roider (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Lecture on the first SFB/TR 15 meeting, Gummersbach, July, 18 - 20, 2004: We report results of an internet experiment designed to test the theory of informational cascades in financial markets (Avery and Zemsky, AER, 1998). More than 6400 subjects, including a subsample of 267 consultants from an international consulting firm, participated in the experiment. As predicted by theory, we find that the presence of a flexible market price prevents herding. However, the presence of contrarian behavior, which can (partly) be rationalized via error models, distorts prices, and even after 20 decisions convergence to the fundamental value is rare. We also report some interesting differences with respect to subjects' fields of study. Reassuringly, the behavior of the consultants turns out to be not significantly different from the remaining subjects.
urn:nbn:de:bvb:19-epub-13539-6
Keywords: C92; D8; G1; 330; informational cascades; herding; contrarians; experiment; internet